Notes for a Critique to the Program of the Sociology of Emotions - Vivian Romeu (Budapest International Research and Critics University, 2020)
This work elaborates a critique of the current program of the sociology of emotions that is located in the conceptual space around the definition of society. This impacts on the good development of concepts such as social interaction and cognition, fundamental to think about the role of the social in the emotional and emotional life of the subjects, in turn affecting the development of the sociology of emotions program which currently results incomplete and insufficient to explain the relationship between emotion, individual and society.